Silver dressings in the treatment of exsudative wounds - a systematic review - Silva Leite, Filipe Augusto; Senna Araújo Brito, André (Revista Feridas, 2021)
Objective: To compare the effects of silver dressings versus silver-free dressings in reducing exudate in wounds. In view of the emergence, in recent years, of silver dressings in the treatment of exudative wounds, thus making a survey of evidence about this fact valid. Method: This work is a systematic review guided by the guidelines of Prisma, using the database MedLine/Pubmed, SciELO and manual search. Randomized trials in English, Portuguese and Spanish were included, comparing silver dressings versus silver-free dressings in reducing wound exudation. CONSORT was used as a method of evaluating the quality of articles, including the ones with a score of at least 70%. Results: Four studies were found that compared the use of silver dressings to reduce wound exudation. All of them showed superiority in favour of silver dressings due to the decrease in the level of exudate. The main risks of bias considered are those of attrition, publication, detection and performance. Conclusion: Treatment with silver dressings proved to be superior to treatment with dressings that do not use silver in reducing exudation in burns, surgical wounds, ulcers, diabetic and infected feet. However, studies with a larger sample value are still needed to clarify a better approach.